2003
DOI: 10.1002/ajim.10202
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with women's risk of rape in the military environment

Abstract: Violence towards military women has identifiable risk factors. Work and living environments where unwanted sexual behaviors occurred were associated with increased odds of rape. Officer leadership played an important role in the military environment and safety of women. Assailant alcohol and/or drug abuse at time of rape was notable. Interventions and policies based on modifiable environmental risk factors are needed to increase protection for women in the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
146
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 168 publications
(152 citation statements)
references
References 35 publications
(45 reference statements)
5
146
1
Order By: Relevance
“…The identification of sexualized workplaces as a risk factor for MSA highlights the generalized impact of a salient normative view of women as a sexual resource (Sadler et al, 2003). Complete abstinence from heterosexual activity is probably the strongest signal that a woman does not want to be viewed by men as a potential sexual partner.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The identification of sexualized workplaces as a risk factor for MSA highlights the generalized impact of a salient normative view of women as a sexual resource (Sadler et al, 2003). Complete abstinence from heterosexual activity is probably the strongest signal that a woman does not want to be viewed by men as a potential sexual partner.…”
Section: Resultsmentioning
confidence: 99%
“…Journal of Trauma & Dissociation, 12:305-323, 2011 313 (Sadler et al, 2003), many women reported choosing the sexual strategy of pairing to lessen their risk of MSA. For this article, we have drawn on the naturalistic data of narratives to develop a preliminary typology of military women's experiences that fleshes out our framework.…”
Section: Military Women's Experiences: a Preliminary Samplingmentioning
confidence: 99%
See 3 more Smart Citations